THE ROLE OF INFORMATION SYSTEMS IN AUTOMATING INTERNAL AUDIT ACTIVITIES IN HIGHER EDUCATION INSTITUTIONS - Avazbek Akhmadalievich Mamatqulov (Innovate Conferences, 2025)
In the context of digital transformation, internal audit has become a critical component for ensuring transparency, efficiency, and accountability in higher education institutions. Traditional methods of auditing—relying on manual documentation and delayed reporting—are increasingly inadequate in handling the complexity and scale of modern university operations. This paper explores the role of information systems in automating internal audit activities within higher education, focusing on the integration of ERP systems, automated risk detection tools, and electronic document circulation. The research outlines both the theoretical underpinnings and practical implications of using digital platforms to enhance audit performance, reduce human error, and ensure timely decision-making. The study emphasizes the need for policy alignment, technical capacity-building, and institutional readiness to fully leverage digital audit systems.
Keywords: Internal audit, higher education, information systems, automation, ERP, digital transformation, audit management systems, electronic governance.